Psychometric validation of the Cystic Fibrosis Impact Questionnaire (CF-IQ): A patient-reported outcome assessing impacts of cystic fibrosis - Daniel Serrano; Alyssa Uzumcu; Maya Gerstein; Nicolai D. Ayasse; Ella Engstrom; Frederick B. Barnes; Charles Iaconangelo; Teja Thorat; Lisa J. McGarry; Isabelle Sermet-Gaudelus (PLoS ONE, 2025)
The Cystic Fibrosis (CF) Impact Questionnaire (CF-IQ) was qualitatively developed to assess the impact of CF in the context of treatment advancements and increased longevity. This study reports the CF-IQ validation. In this noninterventional validation study, people with CF completed the 40-item CF-IQ and validating patient-reported outcome measures (PROMs) via electronic diaries at enrollment (baseline) and at the 4-week follow-up. Validation consisted of modern methods and focus groups to finalize structural validity, and classical methods to assess internal consistency [1–3], test-retest reliability [4,5], concurrent validity [5], and known-groups validity [5] of the CF-IQ. At baseline, 214 adults completed the survey; 193 completed the follow-up survey. Unidimensional item response theory (IRT) models were separately fit to 5 prespecified domains (Control and Burden of CF Treatment Impacts, Physical Activity Impacts, Social Activity Impacts, Emotional Impacts, and Work/School Limitation Impacts). IRT local dependence (LD) statistics identified 17 redundant items. Two independent CF-patient focus groups (14 total patients) confirmed these findings, and the 17 items were dropped. Each domain defined on the final 23 items achieved the criterion of exact model fit as measured by the root mean squared error of approximation (RMSEA, values = 0), Internal consistency (Cronbach’s α) values ranged from 0.81 to 0.89, 4 of 5 domains achieved acceptable test-retest reliability, with intraclass correlation coefficient (ICC) values ≥ 0.7, acceptable concurrent validity was achieved for all domains, and known-groups validity was established. The novel CF-IQ is a psychometrically robust PROM capturing patient-centric impacts of CF in the context of the current standard of care.